2017
DOI: 10.1371/journal.pone.0174511
|View full text |Cite
|
Sign up to set email alerts
|

The risk of clopidogrel resistance is associated with ABCB1 polymorphisms but not promoter methylation in a Chinese Han population

Abstract: The goal of our study was to investigate the contribution of ABCB1 expression to the risk of clopidogrel resistance (CR). Platelets functions were measured using the Verify-Now P2Y12 assay. Applying Polymerase Chain Reaction–Restriction Fragment Length Polymorphism (PCR-RFLP), the single-nucleotide polymorphisms (SNPs) was tested. Using bisulphite pyrosequencing assay, we investigated the association of the ABCB1 DNA methylation levels and CR. It was shown that female, hypertension, and lower albumin levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 53 publications
0
31
1
1
Order By: Relevance
“…The phenomenon of clopidogrel resistance was influenced by many kinds of extrinsic factors (environment, comorbidities, drug interactions, and so on) and intrinsic factors that may contribute to CR . For instance, our former study indicated that the male gender, higher albumin in males, and hyperlipidaemia decreased the CR incidence . Another study found that chronic kidney disease (CKD) appeared to be related to a poor clopidogrel response and a higher risk of stent thrombosis in PCI patients with diabetes .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The phenomenon of clopidogrel resistance was influenced by many kinds of extrinsic factors (environment, comorbidities, drug interactions, and so on) and intrinsic factors that may contribute to CR . For instance, our former study indicated that the male gender, higher albumin in males, and hyperlipidaemia decreased the CR incidence . Another study found that chronic kidney disease (CKD) appeared to be related to a poor clopidogrel response and a higher risk of stent thrombosis in PCI patients with diabetes .…”
Section: Discussionmentioning
confidence: 93%
“…For instance, ABCA1 DNA methylation was a predictive biomarker for the CAD development and was independent of plasma lipid concentration . Since 2014, several studies have explored the influence of DNA methylation in ABCB1 , P2Y12 , and cytochrome P450 enzymes on CR. This time, we chose PON1 as the target gene and found some significant results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacogenomics Implementation Consortium (CPIC) guidelines [13], as well as covering new 26 variants reported in recent publications [3][4][5][6]15] (Table 1). Use of a polymerase chain reaction (PCR) 27…”
Section: Response the Assay Contained Genetic Variants Reported As Cmentioning
confidence: 99%
“…Both CYP2C19 and CYP2C9 are 5 polymorphic genes with more than 30 known alleles [1]. Moreover, recent publications suggest that 6 other genes are also associated with variable drug response, including B4GALT2 [3] and ABCB1 [4,5] 7…”
Section: Introductionmentioning
confidence: 99%